Adderall and Pregnancy: Neonatal Outcomes Following Prenatal Prescription Mixed Amphetamine Exposure [36C]. (May 2018) - Rose, Sherrill; Borowski, Kristi S.; White, Wendy M.; Hathcock, Matthew; Rivera-Chiauzzi, Enid
Abstract : INTRODUCTION: Increasing numbers of pregnant women are being treated for ADHD. The safety of ADHD medications in pregnancy have not been well studied, although studies suggest that methylphenidate use may lower birthweight compare to unexposed newborns. Our primary outcome was to evaluate if birthweight was lower among infants of women utilizing Adderall in our academic institution. METHODS: Maternal and infant pairs exposed to Adderall between January 2005 and December 2015 was identified in EMR based on active medication list during pregnancy. Patients were matched 2:1 with unexposed controls of similar age, gestational age at delivery, parity, infant sex and date of delivery. All charts were reviewed for known causes of IUGR or low birthweight. Statistical analysis of infant birthweight was done using generalized estimating equation blocking on matching. Medical histories were analyzed using Chi-Square test or Fishers exact test as appropriate. RESULTS: We identified 53 exposed pairs. The difference in mean birthweight for exposed vs unexposed infants was 26.9g which is not statistically or clinically significant (95% CI, P-value: (-141, 195), 0.75). A statistically significant difference was noted for exposed vs unexposed mothers for comorbid psychiatric illness and history of substance abuse (p = <0.0001). CONCLUSION: As Adderall use increases among childbearing women, understanding the risk to infants is crucial. With a limited sample size, our study suggests no significant difference in birthweight, which is a concern for women requiring medication in pregnancy. Women using Adderall may have higher rates of comorbid psychiatric disorders and substance use and may benefit from early screening.